2020
DOI: 10.1163/22125868-12340124
|View full text |Cite
|
Sign up to set email alerts
|

Students as Partners: A New Ethos for the Transformation of Teacher and Student Identities in Chinese Higher Education

Abstract: Engaging students as partners (SaP) in teaching and learning is a growing arena of practice that shapes the mutually beneficial student-teacher relationship. Redefining student-teacher identities in pedagogical practice is one of the key implications of SaP. In the past decade, Chinese higher education institutions have paid increasing attention to student-centred pedagogies. Understanding and investigating new interpretations of student-teacher identities underpins the shift toward such pedagogical practices.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…This shows that students have less decision-making power in their education, although they are provided opportunities to give feedback actively. Nonetheless, there is evidence of gradual improvement as more Chinese academics have recognised these missing opportunities for students to be a part of pedagogical decision-making (Liang et al, 2020). For example, advocated that "students should be empowered to express their views on the design and delivery of teaching and learning" (p. 52), suggesting more active feedback.…”
Section: Quality Assurance: Conversations Consultants and Student Representativesmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that students have less decision-making power in their education, although they are provided opportunities to give feedback actively. Nonetheless, there is evidence of gradual improvement as more Chinese academics have recognised these missing opportunities for students to be a part of pedagogical decision-making (Liang et al, 2020). For example, advocated that "students should be empowered to express their views on the design and delivery of teaching and learning" (p. 52), suggesting more active feedback.…”
Section: Quality Assurance: Conversations Consultants and Student Representativesmentioning
confidence: 99%
“…The changing tides in Chinese higher education policy toward student-centred approaches over the past few decades are re-shaping understandings about the roles of students and academics. For example, Liang et al (2020) explored academic identities in Chinese universities and found "a move toward more participatory and relational pedagogies that value the contributions of students in the learning and teaching process" (p. 141). Furthermore, a scoping review of SaP in Asia found that "SaP is challenging, and will be challenged by, conventional higher education norms currently constructing learner-teacher interactions in Asian countries" (Liang & Matthews, 2021, p. 560).…”
Section: Implications For Further Researchmentioning
confidence: 99%
“…Meanwhile, on the other hand, college organizations have characteristics that indicate the role and position of lecturers as discussion partners for students during the teaching and learning process. In addition, lecturers are individuals with specific knowledge and skills in certain disciplines, so during teaching, lecturers are given greater flexibility by the head of the university or dean to achieve specific learning goals (Liang et al 2020). Therefore, examining the instructional leadership practices and their impacts on job satisfaction and organizational commitment of lecturers is interesting to study.…”
Section: Introductionmentioning
confidence: 99%
“…Confucius’ envisioning of guan -hexagram in the act of teaching-learning movement signifies that the ordering of teacher-student is of hierarchical importance, which is seen as different from a modern democratic representation, and thus entails divided opinions in current China (Liang et al, 2020). Zhao argues in Chapter 6 that this is an example of utilizing a comparative cultural perspective to view teacher-student relationship, i.e.…”
mentioning
confidence: 99%